Analisis Kepuasan Pengguna Atas Layanan Telemedicine Kesehatan Melalui Aplikasi Halodoc - Anggeu Agesti Amelia (Economics and Digital Business Review, 2024)
In the current digital era, there have been significant changes in information and communication technology in the medical field through telemedicine services such as the Halodoc program. The aim of this research is to determine user satisfaction with health telemedicine services through the Halodoc application and the factors that influence this satisfaction. The research method used is a qualitative approach that uses data collection techniques in the form of documentation and literature reviews. Based on a survey of 35 respondents, the majority of users gave positive reviews of the Halodoc service. Factors influencing user satisfaction were identified as responsiveness, service quality, ease of use, service availability, technical quality, and communication with stakeholders. The results of this research provide an in-depth understanding of the views and experiences of users of telemedicine services through the Halodoc program and can be used as practical guidance. to improve the quality of health services. In addition, the results of this research can be a reference for companies and telemedicine developers to improve service quality and strengthen the health system as a whole.